DETERMINANTS OF AUDIT QUALITY AMONG LISTED FIRMS IN NIGERIA: EVIDENCE FROM NON-FINANCIAL FIRMS (Journal of Global Accounting, 2024)
This study examined the determinants of audit quality of listed non-financial firms in Nigeria. To achieve this objective, research questions and hypotheses were designed in line with five specific objectives. Relevant concepts were reviewed along with the review of empirical literature. The research design is ex post facto and relevant statistical tools were employed to analyze the data and the hypotheses were tested using probit regression technique. Based on the result from the analytical procedure of this study, it was observed that in testing the relationship between audit fee and audit quality of listed non-financial firms in Nigeria, the computed chi2 is 281.29 and a p-value of 0.0000 which shows a significant positive relationship between audit fee and audit quality of listed non-financial firms in Nigeria hence the null hypothesis was rejected. Additionally, in testing the relationship between firm size and audit quality, the computed p-value stood at 0.0000 hence, the study rejects the null hypothesis that the size of the firm does not have significant influence on audit quality of listed non-financial firms in Nigeria. The relationship between agency cost and audit quality recorded insignificant relationship having a p-value of 0.3768 this is why the null hypothesis that there is no significant relationship between agency cost and audit quality of the listed non-financial firms in Nigeria was accepted. In testing the null hypothesis, that there is no relationship between audit independence and audit quality of listed non-financial firms in Nigeria the p-value stood at 0.0000 which implies significant relationship between audit independence and audit quality of listed non-financial firms in Nigeria. Lastly, in testing the relationship between firm sector and audit quality the p-value stood at 0.0008. Therefore, the study rejects the null hypothesis that there is no significant relationship between firm sector and audit quality of listed non-financial firms in Nigeria. This study concludes that audit quality is significantly influenced by variables like audit fee, firm size, audit independence and firm sector. Conversely, agency cost exhibited an insignificant though positive relationship with audit quality; thus, helping to moderate threats to auditors independence and quality of service. The study recommends among others that the activities of audit firms should be put under close supervision, especially in the area of auditor remuneration, because this tends to influence the quality of audit
Keywords: Agency cost; Audit quality; Audit firm size; Auditor fee; Auditor independence